PERAN TURNAMEN MOBILE LEGENDS DALAM MENINGKATKAN PENDAPATAN CAFE PRIMADONA, TALANG BABAT, MUARA SABAK - Gunawan, Indra; Daud; Pitri, Alisya; Arif Musthofa, M.; Wandi (Jurnal Dinamika Ekonomi Syariah, 2024)
This study aims to analyze the role of the Mobile Legends tournament as one of the strategies in increasing the income of Cafe Primadona. This tournament was held as a form of business innovation that combines e-sports trends with the culinary industry, so that it can attract visitors, especially teenagers and game lovers. The type of research used is qualitative with a descriptive approach. The research data consists of primary data obtained through direct interviews with café owners, visitors, and tournament participants, as well as secondary data that includes supporting documents related to the implementation of the tournament. Data collection techniques are carried out through observation, interviews, and documentation that is relevant to the topic. The location of the study was at Cafe Primadona, Talang Babat, Muara Sabak. The data collected was analyzed using qualitative methods presented descriptively to provide a clear picture of the impact of the tournament on cafe income. The results of the study show that the Mobile Legends tournament plays a significant role in increasing income through several mechanisms, such as increasing the number of visitors, purchasing food and drinks, and support from sponsors. The income generated not only has a positive impact on the economy of the cafe owner’s family, but also supports the sustainability of operations and the development of cafe business innovations. In addition, the tournament also creates opportunities for collaboration with the local gaming community, further strengthening the appeal of Cafe Primadona as a place to gather and socialize.